P08.07 Identification of stress granule formation as a therapeutic target in chemotherapy treated colorectal cancer. (21st September 2022) - Renner, A; Wolf, B; Krajic, N; Kabiljo, J; Zirnbauer, R; Ammon, D; Strieder, J; Dolznig, H; Fabits, M; Laengle, J; Bergmann, M
Abstract : Background: Under certain stress conditions, such as oxidative stress or nutrient deprivation, specific RNA-binding proteins aggregate with actively translated mRNAs to facilitate translational reprogramming and cell survival. 1 High levels or deregulated activity of these RNA-binding proteins, which include Ras GTPase-activating protein-binding protein 1 (G3BP1) or Y-box-binding protein 1 (YB-1) contribute to tumour progression and metastasis. 2 Inhibition of stress granule (SG) formation may therefore exert a synergistic effect with cytotoxic chemotherapy. Materials and Methods: Formalin-fixed paraffin-embedded sections from neoadjuvant-treated colorectal cancer (CRC) liver metastasis patients (n=33) were immunohistochemically (IHC) stained for YB-1. CRC cell-lines as well as organoids and tissue slice cultures from surgical specimen were treated with oxaliplatin/5-fluorouracil alone or in combination with the histone deacetylase inhibitor (HDACi) MS-275. Incubation with arsenic acid served as positive control for SG aggregation. Immunofluorescence co-staining of YB-1 and G3BP1 was used to detect SG formation. Cell viability and apoptosis induction were analysed using viability (cellular adenosine triphosphate) and cytotoxicity (lactate-dehydrogenase release) assays, flow-cytometry (active caspase 3, viability dye) and IHC (haematoxylin & eosin, active caspase 3, Ki-67). Results: In the cohort of CRC liver metastasis patients, YB-1 protein expression was a negative predictor for overall survival. Oxaliplatin-based chemotherapy induced SG formation in CRC cell-lines and primary tumour tissue culture. Pre-treatment with the HDACi MS-275 prevented stress-granule aggregation and increased the sensitivity of CRC cell lines to oxaliplatin. Conclusions: Clinical data and CRC cell-line or primary tissue cultures identify SG formation as a resistance factor for chemotherapy and as a therapeutic target in CRC. References: Protter, D.S.W. and R. Parker, Principles and Properties of Stress Granules . Trends Cell Biol 2016;26 (9): p. 668–679. El-Naggar, A.M., et al . Translational Activation of HIF1alpha by YB-1 Promotes Sarcoma Metastasis . Cancer Cell 2015; 27 (5): p. 682–97. Disclosure Information: A. Renner: None. B. Wolf: None. N. Krajic: None. J. Kabiljo: None. R. Zirnbauer: None. D. Ammon: None. J. Strieder: None. H. Dolznig: None. M. Fabits: None. J. Laengle: None. M. Bergmann: None.